Improvement of 2.8 μm laser performance on LD side-pumped LuYSGG/Er:LuYSGG/LuYSGG bonding crystal. (February 2023) - Zhang, Huili; Bian, Jintian; Sun, Dunlu; Luo, Jianqiao; Quan, Cong; Hu, Lunzhen; Han, Zhiyuan; Dong, Kunpeng; Qiao, Yang; Cheng, Maojie; Chen, Yuwei
Highlights: Laser performance of LD side-pumped Er:LuYSGG bonding crystal was demonstrated. Maximum output power of 20.76 W is achieved and improved effectively by bonding. M 2 factors of 6.80/6.74 of the bonding crystal are better than that of un-bonding one. Er:LuYSGG bonding crystal is a promising 2.8 μm gain element operated at high power. Abstract: We demonstrate the laser performance of 970 nm LD side-pumped LuYSGG/Er:LuYSGG/LuYSGG bonding crystal in a frequency range of 50–800 Hz. The thermal distribution simulation implies that the bonded Er:LuYSGG crystal possesses a higher cooling efficiency compared with the un-bonded one. The maximum average power of 20.76 W is realized at a frequency of 150 Hz and a pulse width of 200 μs, corresponding to a slope efficiency of 23.94 % and optical-to-optical conversion efficiency of 19.22 %. A single laser wavelength of 2797.5 nm is observed. The M 2 factors of the bonding rod are 6.80/6.74, indicating a relatively high beam quality. Therefore, the LuYSGG/Er:LuYSGG/LuYSGG bonding crystal exhibits an improvement of laser performance operated at 2.8 μm due to excellent heat dissipation ability, which is a promising gain element and can be applied to the harsh radiation environment.